1997
DOI: 10.1007/s002590050197
|View full text |Cite
|
Sign up to set email alerts
|

Limited value of fluorine-18 fluorodeoxyglucose positron emission tomography for the imaging of neuroendocrine tumours

Abstract: Scintigraphy using [111In-DTPA-d-Phe1]-pentetreotide or pentavalent technetium-99m-dimercaptosuccinic acid [99mTc(V)-DMSA] has been shown to localize well-differentiated and slowly growing neuroendocrine tumours, whereas increased fluorodeoxyglucose (FDG) uptake is associated with malignancy. The aim of this study was to compare the value of fluorine-18 FDG positron emission tomography (PET) with that of somatostatin receptor scintigraphy (SS-R) and dual-radionuclide scintigraphy [SS-R and 99mTc(V)-DMSA = DNS]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
131
0
18

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(159 citation statements)
references
References 6 publications
8
131
0
18
Order By: Relevance
“…For MIBG, 99mTc-dimercaptosuccinic acid and SRS, a proportion of patients ranging between 30-80% had unidentified lesions despite the biological evidence of postoperative disease persistence (Clarke 1988, Udelsman et al 1989, Hoefnagel et al 1991, Celentano et al 1995, Anthony et al 1996, Baudin et al 1996, Adams et al 1998a, Berna et al 1998, Arslan et al 2001. FDG-PET seems to be more informative than CIT and other functional techniques, especially in detecting postoperative persistent or relapsing MTC lesions (Musholt et al 1997, Adams et al 1998b, Diehl et al 2001, Szakall et al 2002, de Groot et al 2004). However, the detection rate of postoperatively persistent or recurrent MTC remains low for all the imaging modalities investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For MIBG, 99mTc-dimercaptosuccinic acid and SRS, a proportion of patients ranging between 30-80% had unidentified lesions despite the biological evidence of postoperative disease persistence (Clarke 1988, Udelsman et al 1989, Hoefnagel et al 1991, Celentano et al 1995, Anthony et al 1996, Baudin et al 1996, Adams et al 1998a, Berna et al 1998, Arslan et al 2001. FDG-PET seems to be more informative than CIT and other functional techniques, especially in detecting postoperative persistent or relapsing MTC lesions (Musholt et al 1997, Adams et al 1998b, Diehl et al 2001, Szakall et al 2002, de Groot et al 2004). However, the detection rate of postoperatively persistent or recurrent MTC remains low for all the imaging modalities investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In general, however, rapidly metabolizing cells take up 18 Ffluorodeoxyglucose, so this agent cannot detect pheochromocytoma specifically. 16 One might expect that a sympathomimetic amine, such as 11 C-hydroxyephedrine, would have greater specificity than 18 F-fluorodeoxyglucose, because of the requirement for visualization of uptake by the plasma membrane and intracellular vesicular monoamine transporters. 11 C-Hydroxyephedrine PET scanning can detect pheochromocytoma rapidly (in 2 to 5 minutes) and clearly in most but not all patients, visualizing more lesions with better contrast than by using 131 I-metaiodobenzylguanidine.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) is of limited value in well-differentiated NETs as these tumors often have near-normal glucose turnover. 8 As both 18 F-FDG and 68 Ga-DOTATATE exploit distinct tumor characteristics it is possible that they may be complementary for tumor staging. Higher-grade NETs may show higher metabolic turnover and lose expression of SSRs.…”
mentioning
confidence: 99%
“…To date, however, only a few small series have correlated FDG and/or somatostatin receptor scintigraphy (SSRS) with tumor grade. [8][9][10][11] Aim The purpose of this study was to compare the performance of 68 Ga-DOTATATE and 18 F-FDG in confirmed NET and correlate uptake with tumor grade on histology.…”
mentioning
confidence: 99%